A single step transesterification process to produce biodiesel from the spent cooking oil - Indah Thuraya, Herman; Khairuddin, Md Isa; Naimah, Ibrahim; Farizul Hafizb, Kasim; Mohd Aizudin, Abd Aziz (IOP Publishing Ltd, 2021)
A direct process of transesterification has been carried out to produce high yields of biodiesel. Conversion of waste cooking oil to methyl esters was performed using potassium hydroxide-glycerol (KOH-Gly) as a catalyst. KOH-Gly was produced by mixing KOH and glycerol at a mass ratio of 1:20 at a temperature of 80 oC for 120 minutes. The process of transesterification was performed at a reaction temperature of 60 oC, a molar ratio of oil to methanol of 1:6, 2% wt KOH-Gly catalytic loading for 30 minutes. This process resulted in a waste cooking oil conversion yield of about 97-98% to biodiesel using KOH-Gly as a catalyst. The two layers of the product were produced without the formation of soap, which facilitated the separation and purification process. Gas chromatography-mass spectrometry was used to analyse the chemical content of biodiesel.